Security and privacy in the Internet of Things : challenges and solutions - Hernández Ramos, José Luis; Skármeta, Antonio (Ambient intelligence and smart environments, 2020)
The Internet of Things (IoT) can be defined as any network of things capable of generating, storing and exchanging data, and in some cases acting on it. This new form of seamless connectivity has many applications: smart cities, smart grids for energy management, intelligent transport, environmental monitoring, healthcare systems, et cetera and EU policymakers were quick to realize that machine-to-machine communication and the IoT were going to be vital to economic development. It was also clear that the security of such systems would be of paramount importance and, following the European Commission?s Cybersecurity Strategy of the European Union in 2013, the EU?s Horizon 2020 programme was set up to explore available options and possible approaches to addressing the security and privacy issues of the IoT. This book presents 10 papers which have emerged from the research of the Horizon 2020 and CHIST-ERA programmes, and which address a wide cross-section of projects ranging from the secure management of personal data and the specific challenges of the IoT with respect to the GDPR, through access control within a highly dynamic IoT environment and increasing trust with distributed ledger technologies, to new cryptographic approaches as a counter-measure for side-channel attacks and the vulnerabilities of IoT-based ambient assisted living systems. The security and safety of the Internet of Things will remain high on the agenda of policymakers for the foreseeable future, and this book provides an overview for all those with an interest in the field.